Long-term outcomes of patients on the 1988 West of Scotland renal transplant waiting list. Issue 1 (February 2015) - Murray, Eleanor C; McMillan, Margaret
Background: The prevalent population with established renal failure continues to grow. Method: Using the Renal Electronic Patient Record, we assess the long-term outcomes of the adult population in the West of Scotland who were awaiting kidney transplantation in 1988 ( n  = 219), and compare the demographics to the 2011 transplant waiting list ( n  = 409). Results: Comparing the 2011 transplant waiting list, there are now more patients, but they are older, more likely to be female, and are more likely to have diabetes as a cause of renal failure. Seventy-four percent received a transplant; of these, 41% of the transplants ultimately failed and the patient returned to dialysis; 39% of patients died with a functioning graft and 20% remain alive with continuing transplant function. Life expectancy for those with renal failure was less than 60 years, significantly lower than the general population, though 29% survived for 20 years, half of these with a functioning kidney transplant and half having returned to dialysis. Conclusion: As survival with a transplant improves, attention is required to reduce the causes of mortality, in particular cardiovascular disease, and malignancy and infection associated with immunosuppression.